SUCCESSES OF TRANSLATED WORKS STAGED AT THE KARAKALPAK STATE THEATER OF YOUNG AUDIENCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Karakalpak State Theater of Young Spectators is one of the most productive theaters in recent years. This article talks about the translated works staged by the theater in recent years and the successes achieved.